Column Sorption Uptake and Regeneration Study; Rare Earth Element Sorbent Uptake and Sorbent Stripping - Lanyk, Tim (Tusaar Corp., 2015)
Study of rare earth element (REE) uptake from geothermal brine simulant by column loading, metal recovery through stripping, and regeneration of column for re-loading. Simulated brine testing.
Keywords: geothermal; Brine; Column; regeneration; REEs; stripping; mineral recovery; removal efficiency; recovery from sorbent; rare earth element; loading; reload